"The Studies are Probably the Best Thing That Garfinkel Ever Wrote." Michael Lynch in Conversation With Dominik Gerst, Hannes Krämer & René Salomon - Lynch, Michael; Gerst, Dominik; Krämer, Hannes; Salomon, René (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
Michael LYNCH is widely known as one of the key figures of ethnomethodology. In this interview, he takes the discussion of GARFINKEL's "Studies in Ethnomethodology" (1967) as an opportunity to take the reader back to California in the 1970s as he shares his personal story of how he became acquainted with Harold GARFINKEL and ethnomethodology as a radical approach on the rise. LYNCH provides an account of ethnomethodology as a distinctive way of researching, writing, talking; which stands in high contrast to conventional social sciences and, which not only has been marginalized by the sociological mainstream at the time it came up, but may be seen as endangered nowadays. As he says in the interview, the tense relationship between ethnomethodology and conversation analysis as a robust field of inquiry can be traced back to this question as well. He reflects upon GARFINKELs central intellectual resources—namely phenomenology and the philosophy of WITTGENSTEIN—and shows how his own work embraces the relationships of ethnomethodology with science and technology studies and actor-network theory. Giving insights into how his work is driven by a confrontation of social theory and philosophy with empirical concreteness, LYNCH discusses concepts such as practice and knowledge which may be seen as in-between-phenomena within this confrontation. Finally, he suggests to continuously reread GARFINKEL's "Studies in Ethnomethodology" as the book provides a rich resource of ideas which especially become productive in light of own research.